(untitled) (City: History, Culture, Society, 2020)
Based on an analysis of the peculiarities of Yuriy Vynnychuk’s novel Tango of Death, the author analyzes the author’s narrative strategies of rethinking the examples of urban history in the 1930s and 1940s, reconstructing the collective and personal memories of citizens on the example of Lviv. The analyzed text of the writer is a significant example of Lviv’s “inscription” into the discourse of memory of modern Ukrainian literature, and therefore has two time sections – the pre-war / military (interwar period, years of World War II) and the modern time. The events under study are studied as the history of the townspeople (in particular, the relationship of the children of the soldiers of the UNR Army, who were shot in 1921 near Bazar), are carriers of different, often conflicting, national identities, a call about the possibilities of reconstructing the memory of the “common” Lviv in the conditions of military-political conflict and a radical aggravation of interethnic relations, as well as the restoration of the memory of the Yanovsky concentration camp. It is argued that the imaginary and real polyphony of relations in pre-war Lviv (as in other cities of Galychyna), as well as the childhood and youth of the heroes of the “historical” part of the novel by Yu. Vynnychuk, are destroyed in September 1939. The events of World War II, described by the example of Lviv, are an important component of urban memory, and the suffering suffered by the heroes of the novel can be defined as one of the powerful determinant elements of national identity. In his novel Yu. Vynnychuk resorts to embodying the body in music, staging the text of the novel as “tango”, thereby creating the score of the polyphonic character of Lviv from the crossroads to the victim city with its inhabitants. By the example of the novel by Yu. Vynnychuk, it is shown that the “Lviv” memory is a marker of the temporal horizon, in particular, the communicative memory conveys the historical experience of the city within the individual biographies of the novel’s protagonists using live memories, direct experience and oral narration. The author of the article suggests considering the writer as a carrier of a mnemonic information resource, one who accumulates memory of the tragic pages of urban history and relays to his contemporaries. An analysis of Yu. Vynnychuk’s novel The Tango of Death shows that, firstly, Lviv is an example of not so much a symbolic but a real place of memory and, secondly, a confirmation of A. Assman’s modern thesis about a place of memory that is “sanctified by the presence of the dead”.